Survey of pharmacists on their roles and perceptions of outpatient parenteral antimicrobial therapy in the United States - Christina G. Rivera; Kristin C. Mara; Monica V. Mahoney; Keenan L. Ryan (Cambridge University Press, 2022)
Abstract Objectives: To define outpatient parenteral antimicrobial therapy (OPAT) clinical pharmacy practice across the United States, specifically pharmacist functions, design of pharmacist involvement, and to compare pharmacist training of those who practice in OPAT to infectious diseases pharmacists who do not. Methods: A survey of a possible 32 questions was emailed to the American College of Clinical Pharmacists (ACCP) Infectious Diseases Practice and Research Network (PRN) e-mail list. Results were focused on US-based respondents. Participants: In total, 87 pharmacists responded; 27 of these pharmacists (31%) practiced in OPAT. Results: Training background did not differ between groups. Programs with an OPAT pharmacist were more likely to have a formal OPAT team compared to those without an OPAT pharmacist (P < .001). OPAT pharmacists were early in their careers with 66.7% practicing <5 years in OPAT. Most OPAT pharmacists (66.7%) practiced at an academic medical center with a median full-time equivalent (FTE) of 0.6. Moreover, 63% utilized a collaborative practice agreement and 81.5% shared job functions with other pharmacist roles, most commonly antimicrobial stewardship. Few OPAT programs involved a dispensing component (28%). The median daily census was 43 patients followed by an OPAT pharmacist. Pharmacists performed a variety of tasks in OPAT. Conclusion: Pharmacist nondispensing involvement in OPAT is an emerging trend in the United States with wide variability in program structure and pharmacist tasks. A ratio of 1 OPAT pharmacist for every 45-70 OPAT patients is proposed to facilitate expansion of pharmacist clinical practice in OPAT.